A study of elective genome sequencing and pharmacogenetic testing in an unselected population. Issue 9 (27th July 2021) - Cochran, Meagan; East, Kelly; Greve, Veronica; Kelly, Melissa; Kelley, Whitley; Moore, Troy; Myers, Richard M.; Odom, Katherine; Schroeder, Molly C.; Bick, David
Abstract: Background: Genome sequencing (GS) of individuals without a medical indication, known as elective GS, is now available at a number of centers around the United States. Here we report the results of elective GS and pharmacogenetic panel testing in 52 individuals at a private genomics clinic in Alabama. Methods: Individuals seeking elective genomic testing and pharmacogenetic testing were recruited through a private genomics clinic in Huntsville, AL. Individuals underwent clinical genome sequencing with a separate pharmacogenetic testing panel. Results: Six participants (11.5%) had pathogenic or likely pathogenic variants that may explain one or more aspects of their medical history. Ten participants (19%) had variants that altered the risk of disease in the future, including two individuals with clonal hematopoiesis of indeterminate potential. Forty‐four participants (85%) were carriers of a recessive or X‐linked disorder. All individuals with pharmacogenetic testing had variants that affected current and/or future medications. Conclusion: Our study highlights the importance of collecting detailed phenotype information to interpret results in elective GS. Abstract : Genome sequencing (GS) of individuals without a medical indication is referred to as elective GS. Among 52 individuals undergoing elective GS, 11.5% (6/52) had pathogenic or likely pathogenic variants that may explain one or more aspects of their medical history, 19% (10/52) had variants that altered the risk of disease in the future, including two individuals with clonal hematopoiesis of indeterminate potential, 85% (44/52) were carriers of a recessive or X‐linked disorder, and 100% of individuals with pharmacogenetic testing had variants that affected current and/or future medications.